Potential drug–drug interactions due to concomitant medicine use among people living with HIV on antiretroviral therapy in Australia. Issue 5 (12th December 2022) - de Oliveira Costa, Juliana; Lau, Stella; Medland, Nicholas; Gibbons, Sara; Schaffer, Andrea L.; Pearson, Sallie‐Anne
Abstract : Aims: We quantified concomitant medicine use and occurrence of potential drug–drug interactions in people living with HIV in Australia who are treated with antiretroviral therapy (ART). Methods: In this cohort study using dispensing claims of a 10% random sample of Australians, we identified 2230 people dispensed ART between January 2018 and December 2019 (mean age 49.0 years, standard deviation 12.0 years, 88% male). We examined concomitant medicine use by identifying nontopical medicines dispensed within 90‐days of any antiretroviral medicine dispensing during a 12‐month follow‐up period. For every antiretroviral and nonantiretroviral pair, we identified and classified possible drug–drug interactions using the University of Liverpool HIV drug interactions database. Results: A total of 1728 (78%) people were dispensed at least 1 and 633 (28%) 5 or more unique medicines in addition to ART in a 12‐month period; systemic anti‐infectives and medicines acting on the nervous system were the most common (68% and 56%, respectively). Among comedicated people, 1637 (95%) had at least 1 medicine combination classified as weak interactions, 558 (32%) interactions requiring close monitoring/dose adjustment and 94 (5%) that should not be coadministered. Contraindication or interactions requiring close monitoring/dose adjustment were more common among people receiving protease inhibitors (50–73% across different antiretrovirals), non‐nucleoside reverse transcriptase inhibitors (35–64%), people using single‐tablet combinations containing elvitegravir (30–46%) and those using tenofovir disoproxil (26–30%). Conclusion: Concomitant medicine use is widespread among people living with HIV in Australia. Despite a relatively low prevalence of contraindicated medicines, almost a third received medicines that require close monitoring or dose adjustment. Abstract :